2021
DOI: 10.1021/acs.est.1c01628
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Pathways of the Selective Catalytic Reduction of NO with NH3 on the α-Fe2O3(012) Surface: a Combined Experimental and DFT Study

Abstract: Fe 2 O 3 -based catalysts have promising potential in the selective catalytic reduction (SCR) of NO with NH 3 with the advantages of environmental friendliness, excellent medium−high SCR activity, good N 2 selectivity, and high SO 2 tolerance. However, the NH 3 -SCR mechanism over Fe 2 O 3 -based catalysts remains highly uncertain and controversial due to the complex nature of the SCR reaction. Herein, the NH 3 -SCR reaction pathways over the α-Fe 2 O 3 (012) surface are elucidated at the atomic level by densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…The climbing-image nudged elastic band (CI-NEB) method is performed to locate the reaction barriers of elementary steps via inserting six intermediate images between the initial and final configurations. 42 The adsorption energy or binding energy ( E (X)) of reactants, products and surface species is defined as E (X) = E slab+X − E slab − E X where E X , E slab and E slab+X are energies of the adsorbates, the clean slab and the slab with the adsorbates, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The climbing-image nudged elastic band (CI-NEB) method is performed to locate the reaction barriers of elementary steps via inserting six intermediate images between the initial and final configurations. 42 The adsorption energy or binding energy ( E (X)) of reactants, products and surface species is defined as E (X) = E slab+X − E slab − E X where E X , E slab and E slab+X are energies of the adsorbates, the clean slab and the slab with the adsorbates, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The climbing-image nudged elastic band (CI-NEB) method is performed to locate the reaction barriers of elementary steps via inserting six intermediate images between the initial and nal congurations. 42 The adsorption energy or binding energy (E(X)) of reactants, products and surface species is dened as…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%
“…With the proceeding of the reaction, more NH 4 + species facilitated the adsorption of NH 3 , but the accumulation of inactive N 2 O 4 resulted in a decrease in the SCR activity. For the Pb-poi catalyst, plenty of active nitrate including NO 2 (1606 cm –1 ), monodentate nitrate (1522 and 1245 cm –1 ), and bridged nitrate species (1346 cm –1 ) were adsorbed on the catalyst surface. , The NO x species began to be consumed, with NH 3 (1586, 1286, and 1253 cm –1 ) and NH 4 + species (1669 and 1439 cm –1 ) appearing upon the same adsorption with NH 3 for 5 min, while it could be found that the intensity of NH 4 + weakened and NO 2 was still detectable on the catalyst surface after the introduction of NH 3 within 30 min. This result demonstrated that the NO x species formed on the surface of the Pb-poi catalyst were more active, but the adsorption of NH 3 was inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…Selective catalytic reduction of NO x with ammonia (NH 3 -SCR) is a state-of-the-art technique for the removal of NO x from diesel vehicle exhaust. [1][2][3][4] Cu-SSZ-13 with a chabazite structure (CHA) exhibits outstanding NH 3 -SCR performance at low temperatures and has been successfully commercialized for the control of NO x from diesel engines. [5][6][7][8][9][10][11][12][13] An in-depth understanding of the NH 3 -SCR mechanism is required for the development of Cu-SSZ-13 catalysts to satisfy the increasingly stringent emission standards.…”
Section: Introductionmentioning
confidence: 99%